2023
DOI: 10.3389/fpubh.2023.1094960
|View full text |Cite
|
Sign up to set email alerts
|

School-based intervention on behavioral intention of adolescents regarding healthy diet in India

Abstract: IntroductionAdolescence is a distinctive period of life when intense physical, psychological, and cognitive development occurs. A healthy diet helps prevent various forms of malnutrition and non-communicable diseases (NCDs) like diabetes, heart disease, stroke, and cancer. The current study aimed to assess the change in behavioral intentions (measured based on the TPB) toward healthy dietary practices through health promotion intervention among adolescents studying in selected schools in an urban area of West … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The application of this approach for implementing GENTAS among students is expected to be more appropriate and effective in reducing obesity rate. This could be introduced as a new approach and could be added to the list of the existing approaches for eating behavior interventions, such as simple intervention [39], diet and exercises [40], intervention addressing food-related impulsivity [41], educational intervention [42], healthy eating behavior [43], web-based nutrition intervention [44], implicit process interventions [45], intervention addressing behavioral intention [46]. Limitations of the current study included the method to collect demographic information of the participants in the time of COVID-19 pandemic, where the information was obtained based on participants' report only.…”
Section: Discussionmentioning
confidence: 99%
“…The application of this approach for implementing GENTAS among students is expected to be more appropriate and effective in reducing obesity rate. This could be introduced as a new approach and could be added to the list of the existing approaches for eating behavior interventions, such as simple intervention [39], diet and exercises [40], intervention addressing food-related impulsivity [41], educational intervention [42], healthy eating behavior [43], web-based nutrition intervention [44], implicit process interventions [45], intervention addressing behavioral intention [46]. Limitations of the current study included the method to collect demographic information of the participants in the time of COVID-19 pandemic, where the information was obtained based on participants' report only.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition education is essential for encouraging healthy eating any strategy focused on changing behavior. Nutrition education in schools during early life is a key factor in uencing students' eating behaviors [30] TPB was used as a theoretical framework in many studies on healthy diets and was found effective in increasing healthy eating intention among adolescents [20,25,27,31]. Another systematic review of the theory of planned behavior in behavior change intervention was conducted by Hardman et al [32].…”
Section: Discussionmentioning
confidence: 99%
“…The calculation also factored in a design effect of 1.5 and included an attrition rate of 10%. Based on a school-based intervention conducted by [27], The standard deviation of attitude toward a healthy diet among the pre-intervention group was 27.15 and among the post-intervention group 18.03 respectively, and the average mean difference was 15.67. Thus, the minimum sample size required in each group was 60.…”
Section: Sample Sizementioning
confidence: 99%
“…First, it expands the scope of research on the TPB in the fields of food and diet consumption. As a social psychological model that can effectively identify and elucidate consumer behaviour and behavioural intention, the TPB has seen applications in the field of food/diet consumption behaviour, but they have focused on organic food purchasing, environmentally friendly food consumption, healthy eating behaviour, and food waste reduction behaviour (Al-Swidi et al, 2014;Visschers et al, 2016;Jha et al, 2023). Meanwhile, our study extends the TPB in terms of health consciousness, environmental concern, and past eating behaviour and applies it to explore the main influencing factors and internal mechanisms of Chinese consumers' intention to adopt SHDP.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The TPB has generally been used to predict consumers' behavioural intentions and has been widely used in related studies on health, pro-environment, and sustainable consumption behaviours (McEachan et al, 2011;Shukri et al, 2016;Tang et al, 2023). Some scholars have used the TPB as a theoretical basis to predict and explain individual intentions regarding healthy or sustainable diets (Visschers et al, 2016;Biasini et al, 2021;Jha et al, 2023). Many of these previous studies have focused on healthy eating intentions, and the few have focused on sustainable eating intentions to reduce food waste.…”
Section: Introductionmentioning
confidence: 99%